Public Investments, Private Profits: Reflections on the Relations Between Business and the State, Based on a Case Study in Mato Grosso - Galvão, Maryanne (Pontifícia Universidade Católica de São Paulo, 2021)
Throughout the 2000s we observed a case of social-environmental conflict that occurred in the northwest of Mato Grosso, in the Juruena valley, involving, on the one hand, an indigenous group and, on the other, businesspeople belonging to a consortium that builds small hydroelectric power stations. As we followed this case, which arose due to the construction of a set of power plants on the Juruena River, we perceived a close relationship between the businesspeople of the electric power generation project - which received large amounts of money in the form of federal government financing - and the State. In this brief article, we seek to highlight some of the issues involving business and the State, the public and the private, that we encountered during our doctoral research, as well as some clues that helped us reflect on the issue.